A Consumption-Oriented Theory of the Demand for Financial Assets and the Term Structure of Interest Rates - Stiglitz, J. E. (Review of Economic Studies, 1970)
Journal Article A Consumption-Oriented Theory of the Demand for Financial Assets and the Term Structure of Interest Rates Get access J. E. Stiglitz J. E. Stiglitz Cowles Foundation, Yale University Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 37, Issue 3, July 1970, Pages 321–351, https://doi.org/10.2307/2296724 Published: 01 July 1970 Article history Received: 01 August 1968 Revision received: 01 November 1969 Published: 01 July 1970